2021
DOI: 10.22456/2316-2171.86693
|View full text |Cite
|
Sign up to set email alerts
|

Percepção Dos Idosos Sobre O Papel Do Enfermeiro Num Centro De Convivência

Abstract: Introdução: O Centro de Convivência de Idosos (CCI) é um espaço  destinado ao bem-estar da pessoa idosa. O acompanhamento de profissionais de saúde, em especial o enfermeiro nesse espaço contribui para promoção da saúde e prevenção de agravos. Objetivo: Compreender a percepção dos idosos quanto a atuação do enfermeiro no Centro de Convivência. Método: Trata-se de uma pesquisa descritiva, exploratória, de abordagem qualitativa realizada em um município da região do Sudoeste do estado de Mato Grosso, com idosos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…6 A study carried out with the elderly revealed that the practices developed by services aimed at the elderly allow the construction of new knowledge and the approximation between the user and the professional, with the nurse being the propeller of a health care model directed to the needs of this patient group, guaranteeing them comprehensive care. 26 Added to this is the fact that women, as they seek the health service more frequently, appear to be closer to the professionals who work there, demonstrating confidence in solving complex cases and/ or preventable, which makes it possible to understand the ideas they share on the subject.…”
Section: Discussionmentioning
confidence: 99%
“…6 A study carried out with the elderly revealed that the practices developed by services aimed at the elderly allow the construction of new knowledge and the approximation between the user and the professional, with the nurse being the propeller of a health care model directed to the needs of this patient group, guaranteeing them comprehensive care. 26 Added to this is the fact that women, as they seek the health service more frequently, appear to be closer to the professionals who work there, demonstrating confidence in solving complex cases and/ or preventable, which makes it possible to understand the ideas they share on the subject.…”
Section: Discussionmentioning
confidence: 99%
“…6 Um estudo realizado com idosos revelou que as práticas desenvolvidas por serviços destinados à terceira idade permitem a construção de novos conhecimentos e a aproximação entre o usuário e o profissional, sendo o enfermeiro o propulsor de um modelo de atenção em saúde direcionado às necessidades deste grupo, garantindo-lhes atenção integral. 26 Soma-se a isso o fato de que as mulheres, ao buscarem com maior frequência o serviço de saúde, aparentam maior proximidade com os profissionais que atuam nele, demonstrando confiança para a resolução de casos complexos e/ou passíveis de prevenção, o que torna possível entender as ideias que compartilham sobre o tema.…”
Section: Discussionunclassified
“…A educação em saúde desempenha, é um papel fundamental na promoção de comportamentos saudáveis e na autonomia dos idosos. Através de atividades educativas, os enfermeiros compartilham conhecimentos, ouvir as fragilidades dos idosos e promover a construção de saberes relacionados ao autocuidado, contribuindo para um envelhecimento ativo e saudável (ANDRADE et al, 2019;SILVA et al, 2020;CASTRO et al, 2018;OLIVEIRA et al, 2020).…”
Section: Categoria 1 -Intervenções De Enfermagem Para O Envelheciment...unclassified